Comparative Study of the Antioxidant Properties of Trolox, Ascorbic Acid and Butyl Hydroxytolene (BHT) by the Methods of Quantum Chemistry - CHABI DOKO, Rodrigue; KPOTA HOUNGUE, MAHOUGBE TATA ALICE; KPOTIN, ASSONGBA GASTON; KUEVI, URBAIN AMAH; ATOHOUN, YACOLÈ GUY SYLVAIN; MENSAH, JEAN-BAPTISTE (My University, 2017)
By functional B3LYP of the DFT, and in two bases set (6-311G (d, p), cc-pDVZ), and by the semi-empirical method AM1 a theoretical study of the antioxidant properties of three molecules (the trolox, the ascorbic acid and butyl hydroxy toluene) was carried out. The electronics parameters as gap HOMO-LUMO, antioxidant power w, hydrophilic index Hy, dipole moment), oxidation reduction potentials, potential of ionization and electronic affinity were calculated, and also thermodynamics parameters as, of Proton Transfer and of Hydrogen Atomic Elimination. The electronic calculated parameters allowed to estimate the powers electron donors and electron acceptors hardness (η), the softness (S), the electronegativity (χ), the electrophilic index (ω) of molecules and to confirm their classifications in the literature according to the oxidizing power. The results of the various calculations have revealed that: Functional B3LYP of the DFT is more appropriate than the semi-empirical method AM1, for this study trolox is the most reductive of the three molecules and can then be used as reference molecule for the evaluation of the antioxidant properties of the bioactive molecules for the trolox and ascorbic acid which have several hydroxyl groups, the most important sites for the manifestation of the antioxidant activity are the hydroxyl groups OH9 and H3 respectively.
Keywords: Trolox; Butyl hydroxy toluene; Ascorbic acid; Antioxidizing activity